Relevansi Hubungan Hukum Pidana Lingkungan Hidup Indonesia dengan Prinsip Sustainable Development Goals - Tantimin, Tantimin (Jurnal Komunikasi Hukum, 2021)
Development is a goal of the Indonesian nation to increase in increasing its growth. Development must be based on the principle of sustainable development based on environmental principles in the Sustainable Development Goals. However, in its implementation, development sometimes slightly ignores environmental aspects, so that the role of environmental criminal law is the juridical basis in carrying out the limits of authority carried out on the environment and as the basis for law enforcement. This research was conducted using the juridical-normative method, where the study of the approach used a conceptual approach. The purpose of this study is to examine whether the development goals in the SDGs have the same goals related to the aspect of law enforcement. The results of this study found that the pillars of the SDGs in terms of realizing environmental-based development must be supported by institutions such as politics, law, and bureaucracy in realizing development and law enforcement that is just. Law enforcement based on Law 32 of 2009 on Environmental Protection and Management which is the result of revision of several previous laws seems to have been able to provide fair law enforcement for the community and the environment.